Absolute instabilities of a finite length vortex street with external axial velocities - Chiu, Tak Wai; Berney, Aaron Hanson (Computer Assisted Methods in Engineering and Science, 2023)
This paper presents a numerical algorithm for the study of the absolute instability of a vortex street with external axial velocities and finite length vortices. The aim is that this will be of relevance to the study of the flow over slender bodies at yaw. The algorithm is based on the vortex dynamics momentum equation. Special core treatments have been implemented to tackle the problem of infinite self-induced velocity. A small perturbation method is then used to formulate the eigenvalue problem.